Johannes Stroebel: Winner of the 2023 Fischer Black Prize - NIEUWERBURGH, STIJN VAN (Journal of Finance, 2023)
Johannes Stroebel is the David S. Loeb Professor of Finance at New York University's Stern School of Business. Johannes joined Stern as an Assistant Professor of Finance in 2013 and received tenure in 2016. He started his career in 2012 as the Neubauer Family Assistant Professor of Economics at the University of Chicago Booth School of Business after earning a Ph.D. in Economics at Stanford University. Stroebel's prolific body of work, which looks more like that of somebody 20 rather than only 10 years out of the Ph.D., spans a broad range of topics and uses a variety of methods. He has made important contributions to at least four areas: household finance, asset pricing, climate risk, and social networks. Several papers forge connections between these areas. I highlight key contributions to each of these research agendas. The first strand of Johannes' work focuses on household finance. In two papers published in the Quarterly Journal of Economics (Agarwal et al. (2015, 2018)), Stroebel combines a large microlevel data set of credit card accounts with careful identification. The first paper finds that regulation that protected consumers by limiting fees was not undone by banks charging higher costs elsewhere, but rather resulted in higher consumer surplus. The second paper uses the cross-section of credit card accounts to show that the monetary pass-through via the bank lending channel is limited because the borrowers with a high marginal propensity to borrow and consume are those for which the banks have a low marginal willingness to lend. Another important paper in household finance is the American Economic Review paper (Giglio et al. (2021b)) that establishes a modest response of financial portfolio decisions to households' beliefs about expected returns. Johannes returns to the topic of consumer credit in a forthcoming Journal of Finance paper (Howell et al. (2023)) on lender automation and racial disparities in credit access. Much of Johannes' work, some of which I describe below, touches on housing, the largest asset in households' portfolios. Stroebel's second main research pillar is asset pricing. In three connected papers, Giglio, Maggiori, and Stroebel infer the discount rates that investors apply to cash flows that accrue in the very far future. Such very long discount rates are important, for example, for analyses of greenhouse gas abatement investments that trade off the uncertain future benefits against current costs (Giglio et al. (2021a)). More on the climate implications below. In traditional financial markets, we have very few very long-lived assets from which to infer long-run discount rates. The authors turn to real estate markets. In Singapore and the United Kingdom, investors can buy houses either as freeholds, which grant perpetual ownership rights to land and structure, or as leaseholds, which grant tradeable temporary ownership rights ranging between 75 and 999 years. From the price difference between freeholds and leaseholds of different maturities, the authors back out a term structure of discount rates under reasonable assumptions on growth rates of rents. The observed price discounts imply low long-run discount rates of 2.6% per year for very far-out payoffs. Combined with the observation that the overall (maturity-weighted) return on housing is around 6% per year, they conclude that the term structure of discount rates is downward sloping (Giglio, Maggiori, and Stroebel (2015)). These discount rate estimates suggest that there was no bubble in these housing markets in the 2000s (Giglio, Maggiori, and Stroebel (2016)). Put differently, the risk premium applied to cash flows in the very far future is high enough to make its present discounted value equal to zero; the transversality condition for long-lived assets is likely to be satisfied. The third and most recent area Johannes has focused on is climate finance, as summarized in a recent review article (Giglio, Kelly, and Stroebel (2021)). A central issue in this literature is how to think of the uncertainty associated with future benefits of climate abatement investments. More economic activity creates larger climate damages as a by-product. But climate risk also directly affects the economy, think of a natural disaster. Under the first view, states of the world with lots of climate change are states of the world with high GDP (Nordhaus (2013)), whereas in the second view, they are states with low GDP (Barro (2015), Weitzman (2012)). Whether states of the world with rapid climate change are good or bad states has major quantitative implications for the discount rate to be used when calculating the benefits of climate mitigation and the social cost of carbon. Giglio et al. (2021a) argue that real estate markets are informative for which discount rate to use when evaluating climate abatement investments. It establishes that real estate returns are risky, performing poorly in low-growth and consumption disaster states. It also documents that real estate values are indeed exposed to climate risk by studying how coastal house prices change when the perception of climate risk increases. A disaster risk model, where economic activity increases the likelihood of a climate disaster and rebounds after a disaster, generates a downward-sloping discount rate curve, consistent with the aforementioned evidence from the real estate market. Since climate abatement investments hedge climate change risk, the appropriate discount rates are below the risk-free rate at all maturities and rising in maturity. Johannes has several more interesting papers in climate finance (Engle et al. (2020), Stroebel and Wurgler (2021), van Benthem et al. (2022), Alekseev et al. (2022)) that zoom in on risk measurement and management. The fourth, and maybe most well-known area of Johannes' research portfolio is his work on how social networks affect economic decision making, summarized in Bailey et al. (2018a) and Kuchler and Stroebel (2021). Together with Theresa Kuchler and other coauthors, Johannes uses Facebook (now Meta) data to construct a social graph of friendship links and shows that this network is important for the transmission of beliefs about all kinds of real outcomes. Their first and best-known paper in this agenda is in the Journal of Political Economy (Bailey et al. (2018b)). It shows that friends' experiences with house price growth shape the homeownership choices and the price paid for houses of their geographically distant Facebook friends. This influence occurs by changing their beliefs. In Bailey et al. (2019), the authors explore how variation in house price beliefs that is induced by the same type of social network variation affects mortgage leverage choice. Kuchler et al. (2022) shows that mutual fund investment decisions are in part determined by social networks. In more recent worth with Raj Chetty, Matt Jackson, Theresa Kuchler, and other coauthors (Chetty et al. (2022a, 2022b)), Johannes investigates that the effect friendship networks have on upward income mobility. They also study the factors that influence interactions across people of different socioeconomic backgrounds and suggest policy interventions that could increase such interactions. The Fischer Black Prize honors individual financial research. It is awarded for a body of work that best exemplifies the Fischer Black hallmark of developing original research that is relevant to finance practice. The winner should either be under age 40, or under age 45 for a winner who had not been awarded a Ph.D. (or equivalent) by age 35. The American Finance Association appreciates the generosity of the original donors who made this prize possible and the recent 2018 donors who helped to substantially increase the endowment. The names of the donors can be found at https://afajof.org/fischer-black-prize/.